Deindustrialization and industry polarization - Michael Sposi; Kei-mu Yi; Jing Zhang (Federal Reserve Bank of Chicago, 2022)
We add to recent evidence on deindustrialization and document a new pattern: increasing industry polarization over time. We assess whether these new features of structural change can be explained by a dynamic open economy model with two primary driving forces, sector-biased productivity growth and sectoral trade integration. We calibrate the model to the same countries used to document our patterns. We find that sector-biased productivity growth is important for deindustrialization by reducing the relative price of manufacturing to services, and sectoral trade integration is important for industry polarization through increased specialization. The interaction of these two driving forces is also essential.
Keywords: F11; F43; O41; O11; 330; Structural change; international trade; sector biased productivity growth